Psychological and pedagogical features of the career growth of vocational education’s teachers - O, Bazyl L.; H. I, Shatkovska; M. МKlymenko; V. O, Radkevych (Opción, 2019)
The article describes the lexical and semantic content of the concepts of «professional career», «professional development», «professional formation», and «professional growth», and considers the relevant definitions via comparative qualitative research methods. As a result, the professional development of the teacher is a long, dynamic, multi-level, and multifaceted process that occurs in four stages of professional growth. In conclusion, in order to achieve good results, it is important for the teacher to learn constantly; to know their strengths and weaknesses, gradually to form in themselves the inner core on which not only professional but also personal development will be built.